Effect of different water biofloc contents on the growth and immune response of gibel carp cultured in zero water exchange and no feed addition system. (29th January 2018) - Zhang, Mingming; Li, Ye; Xu, De‐Hai; Qiao, Guo; Zhang, Jialin; Qi, Zhitao; Li, Qiang
Abstract: This study evaluated the growth and immune response of gibel carp ( Carassius auratus gibelio ) cultured under no feed addition biofloc technology (BFT) system at different total suspended solid (TSS) concentrations (10, 300, 600, 800 and 1, 000 mg/L for group BF0‐NF, BF300‐NF, BF600‐NF, BF800‐NF and BF1000‐NF) for 30 days. The results demonstrated that bioflocs contained rich nutrients, and gibel carp eaten bioflocs showed higher weight gain, specific growth and survival. Digestive enzyme activities such as pepsin and amylase increased significantly in BF300/600/800/1000‐NF groups than those in BF0‐NF group. Antioxidant response including superoxide dismutase and total antioxidant capacity in serum and skin mucus was also enhanced significantly ( p  <   .05). In addition, six immune‐related genes were examined by RT‐qPCR. Compared with BF0‐NF group, expression levels of immune genes intelectin (ITLN), dual specificity phosphatase 1 (DUSP 1), keratin 8 (KRT 8), myeloid‐specific‐peroxidase (MPO), c‐type lysozyme (c‐lys) and interleukin‐11 (IL‐11) were up‐regulated by 78.1‐, 23.9‐, 13.8‐, 138.8‐, 401.8‐ and 91.1‐fold, respectively. The highest expression values were observed at TSS of 600–800 mg/L. This study suggested that bioflocs can be uptaken by gibel carp as a food source, and have a potential to be used as a supplemental food for aquaculture.